2022
DOI: 10.3389/fimmu.2022.900906
|View full text |Cite
|
Sign up to set email alerts
|

RG100204, A Novel Aquaporin-9 Inhibitor, Reduces Septic Cardiomyopathy and Multiple Organ Failure in Murine Sepsis

Abstract: Sepsis is caused by systemic infection and is a major health concern as it is the primary cause of death from infection. It is the leading cause of mortality worldwide and there are no specific effective treatments for sepsis. Gene deletion of the neutral solute channel Aquaporin 9 (AQP9) normalizes oxidative stress and improves survival in a bacterial endotoxin induced mouse model of sepsis. In this study we described the initial characterization and effects of a novel small molecule AQP9 inhibitor, RG100204,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…In line with previous research indicating functional involvement of AQP9 in murine bone marrow dendritic cell maturation in response to inflammatory stimulation [ 37 ] and in LPS-induced endotoxemic shock [ 29 ], a role in multisystemic neutrophil infiltration has been recently reported in a study using a murine model of polymicrobial infection. In these instances, AQP9 was required for the activation of NF-ĸB and the expression of the NLRP3 inflammasome, providing new and important clues on the signaling pathways through which AQP9 is involved in infiltration processes [ 97 ]. In macrophages, AQP9 was shown to be required in phagocytosis promoted by the Pseudomonas aeruginosa lasI/rhlI quorum sensing genes as its expression was strongly increased and the related protein was redistributed to the leading and trailing regions after macrophages were infected with the pathogen [ 82 ].…”
Section: Physiological Roles and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous research indicating functional involvement of AQP9 in murine bone marrow dendritic cell maturation in response to inflammatory stimulation [ 37 ] and in LPS-induced endotoxemic shock [ 29 ], a role in multisystemic neutrophil infiltration has been recently reported in a study using a murine model of polymicrobial infection. In these instances, AQP9 was required for the activation of NF-ĸB and the expression of the NLRP3 inflammasome, providing new and important clues on the signaling pathways through which AQP9 is involved in infiltration processes [ 97 ]. In macrophages, AQP9 was shown to be required in phagocytosis promoted by the Pseudomonas aeruginosa lasI/rhlI quorum sensing genes as its expression was strongly increased and the related protein was redistributed to the leading and trailing regions after macrophages were infected with the pathogen [ 82 ].…”
Section: Physiological Roles and Regulationmentioning
confidence: 99%
“…These data suggest that AQP9 plays an important role in the early acute phase of LPS-induced endotoxic shock involving NF-κB signaling [ 29 ]. AQP9 has been recently demonstrated to have an important pathophysiological role in sepsis, since RG100204, a novel, potent and selective AQP9 inhibitor, reduced septic cardiomyopathy and multiple organ failure in a cecal ligation and puncture (CLP) induced murine model of polymicrobial infection [ 97 ]. RG100204 was found to reduce the activation of NF-ĸB as well as the expression of the NLRP3 inflammasome in the heart and kidney.…”
Section: Potential Relevance Of Aqp9 As Clinical Biomarkermentioning
confidence: 99%
“…First, we have selected the time point of 24 hours post-CLP. It has been shown that at 24 hours organ injury (such as lungs, kidneys, and heart) ( 48 , 50 , 85 87 ), and cytokine levels increase in blood samples of CLP mice ( 48 , 85 ) are comparable to that noted in septic patients ( 49 , 57 ). However, to deepen our understanding of sex-related differences in sepsis, exploring a variety of time points is essential.…”
Section: Discussionmentioning
confidence: 88%
“…However, the regulation played by both insulin and leptin on the gene transcription of AQP9 seems to differ between rodents and humans [167]. Sex-specific dimorphism of hepatic AQP9 expression is found both in rodents and humans consistent with the differences with which the two genders handle glycerol [171][172][173][174].…”
Section: Livermentioning
confidence: 99%